FEATURES OF CONDUCTING LECTURE CLASSES IN ONLINE LEARNING - Nasteka , Tatyana Nikolaevna; Orlova, Olha Volodymyrivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article reveals the features of conducting lecture sessions in online learning and highlights the search for opportunities to improve the delivery of lecture material in an online format.